Synthesis and electrochemical investigation of phthalocyanines with dendritic bulky ethereal substituents - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Metal-free and metallophthalocyanines carrying four dendritic 3,4-bis(benzyloxy)benzyloxy groups on the periphery were prepared by cyclotetramerization of a new precursor, namely 4-[3,4-bis(benzyloxy)benzyloxy]phthalonitrile (2) in the presence of the corresponding divalent metal salts (Zn(II), Co(II)). The novel phthalonitrile derivative 2 was synthesized by the reaction of 4-nitrophthalonitrile and 3,4-dibenzyloxybenzyl alcohol (1), which was prepared by the catalytic reduction of 3,4-dibenzyloxybenzaldehyde with NaBH4 in ethanol. The new compounds were characterized by elemental analysis, together with FT-IR, H-1 NMR and UV-Vis spectra. The electrochemical and in situ spectroelectrochemical measurements showed that while the cobalt phthalocyanine complex (5) gives both metal-based and ring-based redox processes, the metal-free and zinc phthalocyanine complexes (3 and 4) give only ring-based electron transfer processes. An in situ electrocolorimetric method was applied to investigate the colour of the electrogenerated anionic and cationic forms of the novel phthalocyanine complexes carrying bulky ethereal aryloxy substituents. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Electrochemistry; Spectroelectrochemistry; Benzyloxy groups; Synthesis; Dendritic ethereal groups; IN-SITU; METAL-FREE; SPECTROELECTROCHEMICAL CHARACTERIZATION; ELECTROCATALYTIC APPLICATION; HYDROGEN-PRODUCTION; BEARING; METALLOPHTHALOCYANINES; COMPLEXES; COBALT; POSITIONS